Time-trends in assisted and unassisted suicides completed with different methods: Swiss National Cohort (Swiss Medical Weekly, 2015)
OBJECTIVE: The number of suicides assisted by right-to-die associations has increased in recent years in Switzerland. The aim of our study was to compare time trends in rates of assisted and unassisted suicide from 1991–2008. METHODS: The Swiss National Cohort is a longitudinal study of mortality in the Swiss population; based on linkage of census data with mortality records up to 2008. The Federal Statistical Office coded suspected assisted suicides from 1998 onwards; and from 2003 onwards right-to-die associations reported the suicides they assisted. We used Poisson regression to analyse trends in rates of suicide per 100'000 person-years, by gender and age groups (15–34, 35–64, 65–94 years). RESULTS: A total of 7'940'297 individuals and 24'842 suicides were included. In women, rates changed little in the younger age groups but increased in 65–94-year-olds, due to an increase in suicide by poisoning (from 5.1 to 17.2 per 100'000; p